Autopsy findings in the early stage of amyotrophic lateral sclerosis with "dropped head" syndrome. Issue 5 (2nd August 2019) - Tanikawa, Satoshi; Tanino, Mishie; Wang, Lei; Ishikawa, Marin; Miyazaki, Masaya; Tsuda, Masumi; Orba, Yasuko; Sawa, Hirofumi; Matoba, Kotarou; Nakamura, Nishio; Nagashima, Kazuo; Hall, William W.; et al.
Abstract : Dropped head syndrome (DHS) has been rarely observed in amyotrophic lateral sclerosis (ALS), and the neuropathological findings of this condition have almost never been described. The identification of transactivation response DNA‐binding protein 43 kDa (TDP‐43), which binds to RNA/DNA has provided a new method for studying ALS and frontotemporal lobar degeneration (FTLD). Post‐mortem examination of an adult sudden death case of a 71‐year‐old patient who complained of DHS exhibited severe loss of anterior motor neurons in the cervical cord (C4‐6). Loss of nerve fibers of the anterior roots was striking compared with posterior roots, together with marked neurogenic atrophy of posterior muscles semispinalis cervicis. Bunina bodies were found in large neurons of Betz giant cells, but not in the motor neurons of spinal cords, or neurons of bulbar regions. Phosphorylated TDP‐43 (p‐TDP‐43)‐positive structures were detected in the residual neurons of the cervical, thoracic and lumber cords, hypoglossal nucleus, cerebellar dentate nucleus and parahippocampal cortex, together with ubiquitin‐positive inclusions. Phosphorylated Tau positive structures in neuronal cytoplasm were found in the amygdala, entorhinal cortex and parahippocampal cortex, some of which co‐expressed p‐TDP‐43. The medial zone of cervical cords may be the first onset site, and that is the cause of head drop in the early stage of ALS. In spite of detailed examination, the direct cause of sudden death was not verified. This autopsy report revealed the relation of DHS which is a rare clinical manifestation of ALS, and neuropathological findings.